“Politicamedia Authoritarian”: The Post-Idealism of Journalism - Judhariksawan (International Journal of Global Community, 2019)
The mass media is commonly regarded as the fourth estate of democracy, playing a crucial role as a counterweight and supervisor of other democratic institutions. The journalistic ideal of independence and neutrality is often exemplified by the engagement of media outlets and their political owners. However, concerns arise when media ownership and political affiliations turn the media into a pragmatic political tool, particularly during Indonesia's general elections. This issue becomes more pronounced when media owners in Indonesia also hold positions as heads of political parties or are part of political coalitions, a phenomenon termed "Politicamedia Authoritarian" in this study. When the media fails to fulfill its functions and live up to its role, it becomes imperative to reconsider its status as the fourth estate and also reevaluate the legal framework governing the press.